Study of the spin and parity of the Higgs boson in diboson decays with the ATLAS detector - Aad, G; Abbott, B; Abdallah, J; Abdinov, O; Aben, R; Abolins, M; AbouZeid, O S; Abramowicz, H; Abreu, H; Abreu, R; Abulaiti, Y; Acharya, B S; et al. (The European physical journal. C, Particles and fields, 2015)
Studies of the spin, parity and tensor couplings of the Higgs boson in the [Formula: see text], [Formula: see text] and [Formula: see text] decay processes at the LHC are presented. The investigations are based on [Formula: see text] of pp collision data collected by the ATLAS experiment at [Formula: see text] TeV and [Formula: see text] TeV. The Standard Model (SM) Higgs boson hypothesis, corresponding to the quantum numbers [Formula: see text], is tested against several alternative spin scenarios, including non-SM spin-0 and spin-2 models with universal and non-universal couplings to fermions and vector bosons. All tested alternative models are excluded in favour of the SM Higgs boson hypothesis at more than 99.9 % confidence level. Using the [Formula: see text] and [Formula: see text] decays, the tensor structure of the interaction between the spin-0 boson and the SM vector bosons is also investigated. The observed distributions of variables sensitive to the non-SM tensor couplings are compatible with the SM predictions and constraints on the non-SM couplings are derived.